Challenges in Inflectional Morphology: Errors in Plural Formation among EFL Students - Yulianti Sumah; Siska Bochari; Moh. Abraham Akbar Eisenring; Maf'ulah Maf'ulah (Journal of General Education and Humanities, 2026)
Many EFL students continue to struggle with plural formation, particularly in distinguishing regular and irregular noun patterns. This study aimed to identify the inflectional markings most frequently misused in forming plural nouns, to classify inflectional errors, and to calculate the frequency of each error type produced by EFL students. The researchers employed a quantitative descriptive research design. The study population consisted of third-semester students from the English Education Study Program at Tadulako University, with 153 participants selected via simple random sampling. A test consisting of 35 questions was used as the main instrument in this study, and the errors were analysed using Dulay’s Surface Strategy Taxonomy. The findings showed that the irregular form -f/-fe to -ves was the most frequently misused inflectional marking by the students, with a total frequency of 500 errors. Furthermore, 2,358 errors were found in students’ answers across four types: omission, addition, misformation, and misordering. Misformation was the most frequent type of error with a frequency of 1,014 (43.00%), followed by omission with 813 (34.48%), addition with 385 (16.33%), and misordering with 146 (6.19%). These findings indicate that students require more targeted instruction on irregular plural forms. The results highlight the need for teaching strategies that explicitly strengthen students’ morphological understanding to reduce recurring errors in plural formation.